Development of minimal surface on Monkey Saddle, Handkerchief and Thomsen surfaces in tensioned fabric structures / Mohd Nasir Abdul Hadi - Abdul Hadi, Mohd Nasir (2019)
Tensioned fabric structures are typically designed in the form of equal tensioned surface. New form of minimal surface are Monkey Saddle, Handkerchief and Thomsen surface are applied in TFS. These shapes are very versatile in producing structures with a broad variety of surface shapes. This study are applied the model of Monkey Saddle, Handkerchief and Thomsen surface because this model are not studied by other researchers in TFS.